2007
DOI: 10.1089/cpb.2006.9967
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events, Motives for Internet Use, and Social Support Among Digital Kids

Abstract: This study presents the interrelationships between stressful life events, motives for Internet use, social support, and the use of the Internet among a sample of adolescents and children aged 8 to 18 (N = 717). The results show that stressful life events are significantly associated with the consumption of the Internet for mood management (such as entertainment and information seeking) and social compensation (such as recognition gaining and relationship maintenance) motives. Secondly, the more children and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
174
1
24

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(213 citation statements)
references
References 37 publications
14
174
1
24
Order By: Relevance
“…Whang et al, (2003) concluded that people use different behavior repertoires to cope with stressful situations and that internet use may be one such behavior. In support of this argument, Leung (2007) found that playing online games may reduce stress arousal for children and adolescents.…”
Section: Perceived Stressmentioning
confidence: 87%
“…Whang et al, (2003) concluded that people use different behavior repertoires to cope with stressful situations and that internet use may be one such behavior. In support of this argument, Leung (2007) found that playing online games may reduce stress arousal for children and adolescents.…”
Section: Perceived Stressmentioning
confidence: 87%
“…Social support has well established connections to a wide array of positive physical and behavioral health outcomes. 22 Using a cell phone to access support networks has been documented among housed youth 12,13,23 and these data suggest that while the life circumstances of homeless youth differ, they are also using their cell phones to access networks which have the potential to provide social support.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Cell phones have changed the ways adolescents conceptualize belongingness and social connection, 11 creating new avenues for social support 10,12 and coping with stressful life events. 13 Young female adolescents and parents report increased feelings of security as a result of cell phones. 14,15 Some research suggests that merely owning, and not actually using, a cell phone helped adolescents to feel socially connected.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their findings with children and adolescents in Hong Kong, Leung 5 suggested that the new generation of ''digital kids'' had learned to make appropriate use of the Internet at moments of stress (i.e., problems with parents), both for obtaining social support from friends and for relieving stress through online entertainment. Finally, Valkenburg and Peter 6 provided some important clarification of the seemingly contradictory findings of previous studies.…”
mentioning
confidence: 99%